Implementasi Kompetensi Profesional Guru Al Islam dalam Menanamkan Nilai- Nilai Agama Islam pada Siswa SMPIT Fajar Ilahi Bengkong - Frimanti Wahyuni (UNISAN JURNAL, 2024)
This research aims to investigate the implementation of Al Islam teachers’ professional competence in instilling Islamic religious values in SMPIT Fajar Divine Bengkong students. The research method used is descriptive qualitative with a case study approach. Data was collected through observation, interviews and documentation. The main respondents were Al Islam teachers and SMPIT Fajar Divine Bengkong students. The results of the research show that the implementation of Al Islam teachers’ professional competence in instilling Islamic religious values in students is quite good. Al Islam teachers demonstrate a strong understanding of Islamic teaching material and are able to package it in an interesting and relevant way to students’ daily lives. They also use varied teaching methods to increase students’ understanding of Islamic values. However, several challenges were also identified, including limited resources and the use of technology in the learning process. This research provides a deeper understanding of the efforts of Al Islam teachers in instilling Islamic religious values in SMPIT Fajar Divine Bengkong students. The implications of this research can be used as a basis for increasing the professional competence of Al Islam teachers and improving the learning process in the same school, as well as providing input to related parties in improving the quality of Islamic religious education in similar schools.